Transcriptomic Analysis Reveals the Protective Effects of Empagliflozin on Lipid Metabolism in Nonalcoholic Fatty Liver Disease - Ma, Yuting; Kan, Chengxia; Qiu, Hongyan; Liu, Yongping; Hou, Ningning; Han, Fang; Shi, Junfeng; Sun, Xiaodong (Frontiers in Pharmacology, 2021)
Empagliflozin is a novel type of sodium-glucose cotransporter 2 inhibitor with diverse beneficial effects in the treatment of nonalcoholic fatty liver disease (NAFLD). Although empagliflozin impacts NAFLD by regulating lipid metabolism, the underlying mechanism has not been fully elucidated. In this study, we investigated transcriptional regulation pathways affected by empagliflozin in a mouse model of NAFLD. In this study, NAFLD was established in male C57BL/6J mice by administration of a high-fat diet; it was then treated with empagliflozin and whole transcriptome analysis was conducted. Gene expression levels detected by transcriptome analysis were then verified by quantitative real-time polymerase chain reaction, protein levels detected by Western Blot. Differential expression genes screened from RNA-Seq data were enriched in lipid metabolism and synthesis. The Gene Set Enrichment Analysis (GSEA) results showed decreased lipid synthesis and improved lipid metabolism. Empagliflozin improved NAFLD through enhanced triglyceride transfer, triglyceride lipolysis and microsomal mitochondrial β-oxidation. This study provides new insights concerning the mechanisms by which sodium-glucose cotransporter 2 inhibitors impact NAFLD, particularly in terms of liver lipid metabolism. The lipid metabolism-related genes identified in this experiment provide robust evidence for further analyses of the mechanism by which empagliflozin impacts NAFLD.